PERILAKU PETANI KAKAO DALAM PEMANFAATAN KLON UNGGUL DI DESA PONGO KABUPATEN LUWU UTARA - Kulniati Kulniati; Siti Aisa Lamane; Anggra Alfian (Universitas Wahid Hasyim, 2023)
The aim of this study was to analyze the factors driving cocoa farmer behavior through the use of superior clones in Pongo Village, North Luwu Regency. The research method used is a survey method using a questionnaire. The number of samples is 70 respondents, which is done with a qualitative approach. Data analysis uses Smart Partial Least Square (Smart PLS) software. The results showed that length of farming, number of family members and income had a positive but indirect and significant effect on cocoa farmers' behavior when using superior clones in Pongo Village, North Luwu Regency. Media information, government policies, the types of superior clones used, and the existence of farmer groups have a positive but direct and significant impact on cocoa farmers' behavior when using superior clones in Pongo Village, North Luwu Regency.